Finanças comportamentais: estudo sobre hábitos aos clientes bancários de Santana do Livramento - RS - Londero, Henrique Kneipp (2015)
This study aimed to verify if the attendance of individuals in banks interferes in the acquisition of goods and / or banking services. For this, was carried out a Survey research with 107 inhabitants of the city of Santana do Livramento (RS). As data collection instrument was adopted a structured questionnaire, composed of twenty-four questions, which covered demographic and cultural variables and behavioral factors (risk perception, risk behavior, satisfaction, knowledge of banking products and services, attendance, preference ). The analysis was performed using descriptive statistics and performed a nonparametric test. The results showed that the research respondents have a more conservative profile with little experience to carry out their investments and preferring to invest in low-risk products to protect their capital. Hypothesis tests did not show significant differences in the frequency, investor profile and preference when investing. As for attendance, it was noticed that it has no direct connection on the acquisition of banking products and services